Comparison of Bispectral Index and Patient State Index values according to recovery from moderate neuromuscular block under steady-state total intravenous anesthesia - Doyeon Kim (Nature Portfolio, 2021)
Abstract There were insufficient researches of the comparison between Bispectral Index (BIS) and Patient State Index (PSI) values during the recovery of moderate NMB. We investigated the response of these indices during neuromuscular blockade (NMB) reversal by sugammadex under steady-state total intravenous anesthesia (TIVA) using propofol/remifentanil. In this prospective, observational study, patients undergoing laparoscopic cholecystectomy were enrolled. At the end of surgery, after confirming that train-of-four (TOF) count as 1 or 2, we maintained a steady state (BIS value of 40–50). After administration of 2 mg kg−1 sugammadex, BIS, PSI, and electromyography (EMG) signal values were recorded at one-minute intervals for 10 min. The primary outcome was the difference between the changes in BIS and PSI from baseline to a TOF ratio (TOFR) of 90 after sugammadex administration in steady-state TIVA. A total of 48 patients completed this trial. There was no significant difference between the changes in BIS and PSI values from baseline to TOFR 90 (− 0.333 ± 4.955 vs. − 0.188 ± 4.616; 95% confidence interval [CI] − 2.095 to 1.803; p = 0.882). Both BIS-EMG and PSI-EMG values at baseline and TOFR 90 were not statistically different (95% CI − 0.550 to 1.092; p = 0.510, 95% CI − 1.569 to 0.527; p = 0.322, respectively). No patient experienced any complications. Changes in BIS and PSI values after NMB reversal during steady-state TIVA were not significantly different. Both BIS and PSI provide trustworthy values for monitoring anesthetic depth during NMB reversal under TIVA. Trial Registration: This study was registered in the Clinical Trial Registry of Korea ( https://cris.nih.go.kr : KCT 0003805).